Pengaruh Akuntabilitas Publik dan Partisipasi Penyusunan Anggaran Terhadap Kinerja Manajerial dengan Komitmen Organisasi Sebagai Variabel Moderating Pada Organisasi Perangkat Daerah Kota Pematang Siantar - Zulham Afandi Saragi; Widia Astuty; Sukma Lesmana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study explores how public accountability and participation in the budgeting process affect managerial performance, while also Assessing how organizational commitment moderates the relationship in Regional Government Organizations (OPD) of Pematang Siantar City. The research was motivated by discrepancies between budget targets and actual outcomes, along with the low absorption rate of funds in several strategic programs, indicating suboptimal managerial effectiveness An empirical associative Primary data were collected from all OPD units in Pematang Siantar, North Sumatra, using structured questionnaires.. The census sampling technique was used, covering all 30 OPDs, each represented by two officials, resulting in 60 respondents. Data were analyzed using SEM with the PLS method. The results confirm that both public accountability and budget participation have significant positive effects on managerial effectiveness. Furthermore, workplace commitment was proven to fortify the relationship between budget involvement and managerial outcomes. These results underscore that accountability, active involvement, and organizational loyalty are essential drivers in improving managerial effectiveness, consistent with the principles of effective governance..